Titanium alloy gas analysis standard substance and preparation method thereof

Through multiple smelting and forging processes, four titanium alloy gas analysis standard substances with gradients were prepared, which solved the problem of poor quality of titanium alloy gas standard substances in the prior art, achieved accurate control and uniformity of gas element content, and improved the accuracy and cost-effectiveness of analysis and testing.

CN119876691APending Publication Date: 2025-04-25西部超导材料科技股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510022779.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to accurately control the content of each gas element of the titanium alloy gas analysis standard substance, and the domestic titanium alloy gas series standard substances have fewer types and poor quality, resulting in insufficient measurement accuracy and uniformity.

Method used

Using multiple smelting and forging processes, material treatment is carried out through an automatic mixer and a vacuum consumable arc furnace to prepare standard substances with four component gradients, covering the content range required for titanium alloy product analysis, and stress is removed through multiple heat pulling and vacuum annealing.

Benefits of technology

Accurate control of standard substances for gas analysis of titanium alloys is achieved, ensuring the uniformity and stability of each gas element, and improving the accuracy and cost-effectiveness of the test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876691A_ABST
    Figure CN119876691A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium alloy gas analysis standard substance which comprises the following elements in percentage by mass: 6.0%-7.0% of A1, 4.0%-4.5% of V, 0.04%-0.21% of O, 0.004%-0.012% of N and the balance of titanium, and the sum of the mass percentages of the components is 100%. The invention also discloses a preparation method of the titanium alloy gas analysis standard substance, which specifically comprises the following steps: smelting the V55Al alloy, the aluminum shots, the titanium dioxide, the aluminum nitride and the sponge titanium to obtain a cast ingot; the method comprises the following steps: carrying out upsetting and drawing deformation processing on a cast ingot, carrying out deformation processing in a precision forging mode, carrying out hot rolling on an obtained titanium alloy bar, and carrying out three times of hot drawing, annealing stress relief, shearing, uniform mixing and split charging. According to the method disclosed by the invention, the content of each gas element in the titanium alloy standard substance can be accurately controlled, so that the content range required by titanium alloy product analysis is covered, and the uniformity, the stability and the accuracy of the standard substance are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of analysis and detection standard materials, and in particular relates to a titanium alloy gas analysis standard material and also relates to a preparation method of the titanium alloy gas analysis standard material. Background Art

[0002] Titanium alloy is a new type of metal material with the advantages of light weight, high strength and corrosion resistance. It has broad application prospects in aerospace, medicine, energy and environmental protection and other fields. The gas content in titanium alloys, such as oxygen, nitrogen and hydrogen, will directly affect its mechanical properties and corrosion resistance. The oxygen content has a significant effect on the grain size, mechanical properties and chemical properties of titanium alloys. When the oxygen content exceeds a certain range, the oxide particles in the titanium alloy will become larger, thereby affecting the shape and size of the crystals. These changes will further affect the strength and ductility of the material. In addition, the increase in oxygen content will also promote the oxidation reaction of the material, resulting in the formation of more oxides on the surface of the material, reducing its corrosion resistance.

[0003] In order to ensure the performance of titanium alloys, the oxygen and nitrogen content must be strictly controlled during the titanium alloy smelting process. Therefore, it is very necessary to accurately determine the oxygen and nitrogen content during the titanium alloy smelting process. According to the current analytical standards for the determination of titanium alloy gas content at home and abroad, corresponding standard substances are required to calibrate the equipment. The quality of the standard substances used directly determines the accuracy of the test. At present, there are relatively few types of titanium alloy standard substances in China. In the early days, due to the limitations of the preparation process, the quality of the prepared gas standard substances was average. The development of titanium alloy gas series standard substances mainly has the following two difficulties:

[0004] (1) How to accurately control the content of each gas element in titanium alloy standard materials so that it covers the content range required for titanium alloy product analysis. In addition, the content of each element should be distributed as gradually as possible to meet the use needs of standard materials;

[0005] (2) The uniformity, stability and accuracy of the characteristic values ​​of standard materials are important quality indicators. Therefore, the uniformity of standard material ingots is extremely high. How to solve the segregation problem of ingots to ensure the uniformity of gas elements.

[0006] Due to the difficulty in developing titanium alloy gas series standard materials, there are few types of titanium alloy gas series standard materials in China, and currently they mainly rely on imported standard materials. Therefore, it is urgent to develop titanium alloy material gas content analysis standard materials to accurately control and ensure the quality and cost of titanium alloy gas analysis. Summary of the invention

[0007] The purpose of the present invention is to provide a titanium alloy gas analysis standard substance for use in analyzing the content of various gas elements in titanium alloys.

[0008] Another object of the present invention is to provide a method for preparing titanium alloy gas analysis standard material.

[0009] The technical solution adopted by the present invention is that the titanium alloy gas analysis standard material has the following element contents: A1: 6.0% to 7.0%, V: 4.0% to 4.5%, O: 0.04% to 0.21%, N: 0.004% to 0.012%, the remainder is titanium, and the sum of the mass percentages of the various components is 100%.

[0010] Titanium alloy gas analysis standard substances are composed of the following 4 standard substances:

[0011] (1) Ti-ON-1, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.21±0.02wt%, N: 0.010±0.002wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%;

[0012] (2) Ti-ON-2, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.15±0.02wt%, N: 0.004±0.001wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%;

[0013] (3) Ti-ON-3, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.10±0.02wt%, N: 0.008±0.002wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%;

[0014] (4) Ti-ON-4, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.04±0.01wt%, N: 0.004±0.001wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%.

[0015] Another technical solution adopted by the present invention is a method for preparing a titanium alloy gas analysis standard substance, which is specifically implemented according to the following steps:

[0016] Step 1: smelting;

[0017] V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge are mixed and smelted three times to obtain an ingot;

[0018] Step 2: Forging;

[0019] The ingot is subjected to an interactive upsetting and drawing deformation process to obtain a titanium alloy bar of an intermediate billet, and then subjected to a deformation process by a precision forging method to obtain a titanium alloy bar;

[0020] Step 3: rolling and drawing;

[0021] The titanium alloy rod is hot rolled and hot drawn three times to obtain titanium alloy wire, and finally the wire is vacuum annealed to relieve stress;

[0022] Step 4: Shear, mix and package to obtain titanium alloy gas analysis standard material.

[0023] The present invention is also characterized in that:

[0024] In step 1, specifically:

[0025] Step 1.1, ingredients: weigh V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge according to mass percentage, so that the alloy contains 6.0% to 7.0% Al, 4.0% to 4.5% V, 0.04% to 0.21% O, 0.04% to 0.12% N, and the balance is titanium, and the sum of the mass percentages of each component is 100%; V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge are mixed evenly by an automatic mixer;

[0026] Step 1.2, according to the number of electrodes to be pressed, the raw materials that have been evenly mixed are evenly divided into the number corresponding to the number of electrodes to be pressed, and pressed into electrodes to obtain an electrode with a specification of Φ100mm×300mm; repeat this step to obtain a plurality of pressed electrode blocks;

[0027] Step 1.3, placing the obtained several pressed electrodes into a welding box in turn, and when the vacuum degree is drawn to 0.8Pa, filling with argon gas, and when the pressure reaches 6000-8000Pa, using plasma welding to weld the several pressed electrodes into electrode rods;

[0028] Step 1.4, placing the obtained consumable electrode into a vacuum consumable arc furnace for first smelting;

[0029] Step 1.5, after surface machining of the obtained primary ingot, a second smelting is performed in a vacuum consumable arc furnace;

[0030] Step 1.6, after surface machining of the obtained secondary ingot, a third smelting is carried out in a vacuum consumable furnace, and the obtained finished ingot is subjected to skinning and head cutting before proceeding to the next step for forging.

[0031] The smelting process parameters are: controlling the vacuum degree in the furnace within the range of 0.6-0.8 Pa, controlling the melting rate to 5-30 kg / min, the melting voltage to 20-40 V, the arc stabilization 2-28 A AC, and the cycle to 12-22 s.

[0032] In step 2, specifically:

[0033] The obtained ingot is subjected to an interactive upsetting and drawing deformation process to obtain a titanium alloy bar of an intermediate billet, the forging heating temperature is 1000-1200°C, the initial forging temperature is ≥950°C, the final forging temperature is ≥850°C, the air-cooling forging fire times is 3 times, and the final specification of the bar is Φ130±5mm;

[0034] Subsequently, the bar is deformed by precision forging, with a forging heating temperature of 900-1100°C, an initial forging temperature ≥850°C, a final forging temperature ≥650°C, air cooling, 1 forging pass, and a final specification of Φ95±3mm. The surface is polished to obtain a titanium alloy bar.

[0035] In step 3, specifically:

[0036] Step 3.1, using a reversible rolling mill to complete the rolling of the bar; the rolling heating temperature is 850-1050°C, the initial rolling temperature is ≥800°C, the final rolling temperature is ≥650°C, air cooling, the rolling fire is 2 times, and the final specification of the wire is Φ9.8±0.3mm;

[0037] Step 3.2, hot drawing the prepared wire, using a tubular furnace for through-heating, the heating temperature is 800-1000°C, after three hot drawing, the final specification of the wire is Φ3.2±0.2mm, the surface is peeled to obtain titanium alloy wire, and finally the wire is vacuum annealed to relieve stress.

[0038] In step 4, specifically:

[0039] Step 4.1, shearing the obtained titanium alloy wire, controlling the particle length to be 3.30-3.55 mm, and the corresponding particle weight to be 0.1000 g-0.1050 g; after shearing, putting the wire into a roller mill for roller milling;

[0040] Step 4.2, stirring and mixing the tumble-milled particles in an automatic mixer to ensure that the particles are fully mixed;

[0041] Step 4.3, the mixed particles are cleaned by ultrasonic cleaning in ultrapure water for 5-10 minutes, the number of times is not less than 2 times, then ultrasonic cleaning in anhydrous ethanol for 5-10 minutes, the number of times is not less than 2 times, and finally ultrasonic cleaning in acetone for 5-10 minutes, the number of times is not less than 2 times, to ensure that there is no oil stains and other contaminants on the surface;

[0042] Step 4.4, packaging the cleaned particles to obtain titanium alloy gas analysis standard substances.

[0043] The beneficial effects of the present invention are as follows: the method of the present invention includes the steps of batching, electrode pressing, three-time self-consumable smelting, forging, rolling, wire drawing, shearing and packaging. Through strict control of the above steps, the technical difficulties of accurately controlling the content of each gas element of titanium alloy standard material to cover the content range required for titanium alloy product analysis and ensuring the uniformity, stability and quality indicators of the accuracy of the fixed value of the standard material are solved. The titanium alloy gas standard material successfully prepared by the present invention involves four content ranges, which basically covers the gas element range of existing titanium alloys, provides a guarantee for the accurate testing of gas elements, and has high uniformity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a flow chart of the method for preparing titanium alloy gas standard material of the present invention. DETAILED DESCRIPTION

[0045] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0046] Example 1

[0047] The titanium alloy gas analysis standard material of the present invention has the following element contents: A1: 6.0% to 7.0%, V: 4.0% to 4.5%, O: 0.04% to 0.21%, N: 0.004% to 0.012%, the remainder being titanium, and the sum of the mass percentages of the various components being 100%.

[0048] Example 2

[0049] Furthermore, the titanium alloy gas analysis standard material consists of the following four standard materials with composition gradients:

[0050] (1) Ti-ON-1, the weight percentage of each component is: Al: 6.5±0.2wt%, V:

[0051] 4.3±0.2wt%, O: 0.21±0.02wt%, N: 0.010±0.002wt%, the rest are Ti and other impurity elements, the sum of the weight percentages of each component is 100%;

[0052] (2) Ti-ON-2, the weight percentage of each component is: Al: 6.5±0.2wt%, V:

[0053] 4.3±0.2wt%, O: 0.15±0.02wt%, N: 0.004±0.001wt%, the rest are Ti and other impurity elements, the sum of the weight percentages of each component is 100%;

[0054] (3) Ti-ON-3, the weight percentage of each component is: Al: 6.5±0.2wt%, V:

[0055] 4.3±0.2wt%, O: 0.10±0.02wt%, N: 0.008±0.002wt%, the rest is Ti and other impurity elements, the sum of the weight percentages of each component is 100%;

[0056] (4) Ti-ON-4, the weight percentage of each component is: Al: 6.5±0.2wt%, V:

[0057] 4.3±0.2wt%, O: 0.04±0.01wt%, N: 0.004±0.001wt%, the rest are Ti and other impurity elements, and the sum of the weight percentages of each component is 100%.

[0058] Example 3

[0059] The preparation method of the titanium alloy gas analysis standard material of the present invention, that is, the series of gas standard materials Ti-ON-1 to Ti-ON-4 are all prepared using the following operating steps, which are specifically implemented according to the following steps:

[0060] Step 1: Melting, specifically:

[0061] Step 1.1, ingredients: weigh V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge according to mass percentage, so that the alloy contains 6.0% to 7.0% Al, 4.0% to 4.5% V, 0.04% to 0.21% O, 0.04% to 0.12% N, and the balance is titanium, and the sum of the mass percentages of each component is 100%;

[0062] V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge are mixed evenly by an automatic mixer;

[0063] When selecting raw materials, choose grade 0 sponge titanium with a diameter of 3 to 5 mm. Choosing sponge titanium with a diameter of 3 to 5 mm can make the distribution of sponge titanium more uniform.

[0064] In addition, the V55Al master alloy produced by the two-step method can contain lower oxygen in the raw materials.

[0065] The particle sizes of the intermediate alloy, pure metal and sponge titanium should be controlled within a certain range and reasonably matched. The particles of the intermediate alloy and pure metal should be as small as possible to facilitate the uniform distribution of the intermediate alloy in the electrode, while improving the strength of the electrode block and avoiding segregation during ingot melting. In order to more accurately calculate the oxygen and nitrogen brought into the raw materials, the sponge titanium and intermediate alloy need to be sampled at multiple points (n>5) in the raw material barrel to test the chemical composition, and finally the average value is calculated as the final theoretical calculation value.

[0066] Step 1.2, according to the number of electrodes to be pressed, the raw materials that have been mixed evenly are evenly divided into the number corresponding to the number of electrodes to be pressed, and the electrodes are pressed. The pressure of the press is 1200 tons, and an electrode with a specification of Φ100mm×300mm is obtained; repeat this step to obtain a number of pressed electrode blocks, and the obtained electrode blocks are immediately transferred to the drying oven, and the external residence time is not more than 5h to avoid adsorption of water vapor in the air;

[0067] Step 1.3, placing the obtained several pressed electrodes into a welding box in turn, and when the vacuum degree is drawn to 0.8Pa, filling with argon gas (purity not less than 99.99%), and when the pressure reaches 6000-8000Pa, using plasma welding to weld the several pressed electrodes into electrode rods, and immediately smelting the welded electrode rods. If it is not possible to melt immediately, first transfer them to a drying box, and stay outside for no more than 5 hours to avoid adsorption of water vapor in the air;

[0068] Step 1.4, placing the obtained consumable electrode into a vacuum consumable arc furnace for first smelting;

[0069] Step 1.5, after surface machining of the obtained primary ingot, a second smelting is performed in a vacuum consumable arc furnace;

[0070] Step 1.6, after surface machining of the obtained secondary ingot, the third smelting is carried out in a vacuum consumable furnace, and the obtained finished ingot is peeled and cut, and then transferred to the next step for forging;

[0071] During each smelting, the smelting process parameters are: the vacuum degree in the furnace is controlled within the range of 0.6-0.8 Pa, the melting rate is controlled at 5-30 kg / min, the smelting voltage is 20-40 V, the arc is stabilized at 2-28 A AC, and the cycle is 12-22 s;

[0072] Step 2: Forging: The obtained ingot is subjected to an interactive upsetting and drawing deformation process by a fast forging machine to obtain a titanium alloy bar of an intermediate billet, the forging heating temperature is 1000-1200°C, the initial forging temperature is ≥950°C, the final forging temperature is ≥850°C, the air-cooling forging fire is 3 times, and the final specification of the bar is Φ130±5mm.

[0073] Then, the rod is deformed by fine forging, with a forging heating temperature of 900-1100°C, an initial forging temperature of ≥850°C, a final forging temperature of ≥650°C, air cooling, and one forging fire. The final specification of the rod is Φ95±3mm, and the surface is 100% polished to obtain a titanium alloy rod that meets the required size.

[0074] After the prepared rods are sawed, a specimen is taken from the head and tail of the corresponding rods for low-power microstructure inspection. According to the national standard GB / T 5168-2020 "High-power and Low-power Microstructure Inspection Methods for Titanium and Titanium Alloys", the metallographic low-power inspection of the head and tail specimens of the rods is carried out. The low-power inspection results show that the rod structure is dense, uniform, without inclusions, looseness, cracks and other uneven structures.

[0075] Step 3: rolling and drawing, specifically:

[0076] Step 3.1, hot rolling the obtained titanium alloy bar, using a 650 reversible rolling mill to complete the rolling of the bar;

[0077] The rolling heating temperature is 850-1050℃, the initial rolling temperature is ≥800℃, the final rolling temperature is ≥650℃, air cooling, the rolling number is 2 times, and the final wire specification is Φ9.8±0.3mm;

[0078] Step 3.2, hot drawing the prepared wire, using a tubular furnace for through-heating, the heating temperature is 800-1000°C, after three hot drawing, the final specification of the wire is Φ3.2±0.2mm, the surface is peeled to obtain a titanium alloy wire that meets the required size, and finally the wire is vacuum annealed to relieve stress.

[0079] Step 4: Cut, mix and dispense, specifically:

[0080] Step 4.1, shearing the obtained titanium alloy wire into particles of a certain specification by using an automatic shearing machine, controlling the particle length to be 3.30 to 3.55 mm, and the corresponding particle weight to be 0.1000 g to 0.1050 g; after the shearing is completed, putting the wire into a roller mill for roller milling;

[0081] Step 4.2, stirring and mixing the tumble-milled particles in an automatic mixer to ensure that the particles are fully mixed; the stirring time of the automatic mixer is 10 minutes, and the stirring speed is 20 r / min;

[0082] Step 4.3, the mixed particles are cleaned by ultrasonic cleaning in ultrapure water for 5-10 minutes, the number of times is not less than 2 times, then ultrasonic cleaning in anhydrous ethanol for 5-10 minutes, the number of times is not less than 2 times, and finally ultrasonic cleaning in acetone for 5-10 minutes, the number of times is not less than 2 times, to ensure that there is no oil stains and other contaminants on the surface;

[0083] Step 4.4, packaging the cleaned particles to obtain the titanium alloy gas analysis standard substance of the present invention.

[0084] Example 4

[0085] The preparation method of the titanium alloy gas standard material of the present invention, that is, the series of gas standard materials Ti-ON-1 to Ti-ON-4 are prepared using the following operating steps: Figure 1 As shown, the specific implementation steps are as follows:

[0086] Step 1: Smelting

[0087] Ingredients: According to the mass percentage of the titanium alloy gas standard material components in Table 1, weigh V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge, so that the alloy contains 6.0% to 7.0% Al, 4.0% to 4.5% V, 0.04% to 0.21% O, 0.04% to 0.12% N, and the balance is titanium. The sum of the mass percentages of each component is 100%. V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge are mixed evenly by an automatic mixer;

[0088] Table 1 Target mass percentage of titanium alloy gas standard material components (%)

[0089] serial number A1 V O N Ti Ti-ON-1 6.5±0.2 4.3±0.2 0.21±0.02 0.010±0.002 Remain Ti-ON-2 6.5±0.2 4.3±0.2 0.15±0.02 0.004±0.001 Remain Ti-ON-3 6.5±0.2 4.3±0.2 0.10±0.02 0.008±0.002 Remain Ti-ON-4 6.5±0.2 4.3±0.2 0.04±0.01 0.004±0.001 Remain

[0090] According to the number of electrodes to be pressed, the raw materials that have been evenly mixed in the previous step are divided into 15 parts, and the electrodes are pressed. The pressure of the press is 1200 tons, and an electrode with a specification of Φ100mm×300mm is obtained. Repeat this step to obtain the number of electrode blocks to be pressed. The obtained electrode blocks are immediately transferred to the drying oven and stay outside for no more than 5 hours to avoid absorbing water vapor in the air;

[0091] Put the number of electrodes to be pressed obtained in the previous step into the welding box in turn. When the vacuum degree is 0.8Pa, fill it with argon gas (purity not less than 99.99%). When the pressure reaches 6000Pa, use plasma welding to weld the number of electrodes to be pressed into electrode rods.

[0092] The electrode rod obtained in the previous step is placed in a vacuum consumable electrode arc furnace for the first smelting. The vacuum degree in the furnace is controlled within the range of 0.6-0.8 Pa, the melting rate is controlled to be 30 kg / min, the melting voltage is 40 V, the arc is stabilized at 10 A AC, and the cycle is 22 s.

[0093] The electrode rod obtained in the previous step is surface machined and transferred to a vacuum consumable furnace for the second smelting. The vacuum degree is controlled within the range of 0.6-0.8 Pa, the melting rate is controlled at 20 kg / min, the melting voltage is 32 V, the arc is stabilized at 25 A AC, and the cycle is 12 s;

[0094] Put the electrode rod obtained in the previous step into the vacuum consumable furnace for the third smelting to obtain the smelted ingot. Control the vacuum degree in the furnace within the range of 0.6-0.8Pa, control the melting rate to 5kg / min, the melting voltage to 20V, the arc stabilization 16A AC, and the cycle to 10s;

[0095] Initial uniformity inspection. According to the requirements of YS / T 409-2012 "Technical Specifications for Standard Samples" and GB / T15000 "Working Guidelines for Standard Samples", combined with the allowable error given in GB / T4698.7-2011 "Determination of Oxygen and Nitrogen Contents in Chemical Analysis Methods for Sponge Titanium, Titanium and Titanium Alloys", the standard deviation s of a limited number of measurements is calculated, and then compared with the allowable error Δ of the test method GB / T4697.7-2011. When 1.5s≤1 / 2Δ, it is considered that the initial uniformity inspection has passed; otherwise, it is considered that the initial uniformity inspection has failed; the results of the initial uniformity inspection are shown in Table 2 below:

[0096] Table 2 Preliminary inspection results of uniformity of titanium alloy gas standard materials (%)

[0097]

[0098]

[0099] Step 2: Forging

[0100] The obtained ingot is subjected to an interactive upsetting and drawing deformation process by a fast forging machine to obtain a titanium alloy bar of an intermediate billet, the forging heating temperature is 1170°C, the initial forging temperature is ≥950°C, the final forging temperature is ≥850°C, the air-cooling forging fire is 3 times, and the final specification of the bar is Φ130±5mm.

[0101] Subsequently, the bar is deformed by precision forging, with a forging heating temperature of 960°C, an initial forging temperature ≥850°C, a final forging temperature ≥650°C, air cooling, 1 forging pass, and a final specification of Φ95±3mm. The surface is 100% polished to obtain a titanium alloy bar that meets the required size.

[0102] After the prepared rods are sawed, a specimen is taken from the head and tail of the corresponding rods for low-power microstructure inspection. According to the national standard GB / T 5168-2020 "High-power and Low-power Microstructure Inspection Methods for Titanium and Titanium Alloys", the metallographic low-power inspection of the head and tail specimens of the rods is carried out. The low-power inspection results show that the rod structure is dense, uniform, without inclusions, looseness, cracks and other uneven structures.

[0103] Step 3: rolling and drawing;

[0104] The obtained bars were hot rolled and rolled using a 650 reversible rolling mill. The rolling heating temperature was 940°C, the initial rolling temperature was ≥800°C, the final rolling temperature was ≥650°C, air cooling, the rolling fire was 2 times, and the final wire specification was Φ9.8±0.3mm, obtaining a titanium alloy wire that met the required size.

[0105] The prepared wire is subjected to hot drawing, and a tubular furnace is used for heating at a temperature of 850°C. After three hot drawing steps, the final specification of the wire is Φ3.2±0.2mm, and the surface is peeled to obtain a titanium alloy wire that meets the required size. Finally, the wire is vacuum annealed to relieve stress.

[0106] Step 4: Cut, Mix and Aliquot

[0107] The obtained wire is sheared into particles of certain specifications by an automatic shearing machine, and the particle length is controlled to be 3.30-3.55 mm, and the corresponding particle weight is 0.1000 g-0.1050 g. After shearing, it is put into a roller mill for roller milling, and an oil cleaning agent is added during roller milling to clean the oil attached to the surface of the particles;

[0108] The tumbled particles were stirred in an automatic mixer to make them fully mixed. The stirring time of the automatic mixer was set to 10 min and the stirring speed was set to 20 r / min.

[0109] The mixed particles were cleaned by using ultrapure water for 5 min in ultrasound, twice, then using anhydrous ethanol for 8 min in ultrasound, three times, and finally using acetone for 10 min in ultrasound, twice, to ensure that there was no oil stain or other contaminants on the surface;

[0110] The cleaned particles are packaged in glass bottles with inner covers, with 200 particles in each bottle. A desiccant is placed in the bottle, which is then sealed with a thermoplastic film to obtain the titanium alloy gas analysis standard substance of the present invention.

[0111] Example 5

[0112] Homogeneity test. The homogeneity of the standard material is one of its most critical indicators. Therefore, the uniformity test of the gas standard material prepared in the embodiment is carried out. According to the provisions of GB / T15000 "Guidelines for Standard Sample Work" and YS / T 409 "Technical Specifications for Standard Samples", the uniformity test is carried out by random sampling using the single-factor variance analysis method (F method).

[0113] One-way analysis of variance is to randomly select m samples in the same batch, and each sample is analyzed n times (when the total number of samples N ≤ 1000, generally m ≥ 15 and n = 3), that is, divided into m data groups, with n data in each group. First, calculate the within-group variance and the between-group variance Then calculate the statistic F value, and compare it with the critical value F0 of the statistic F and make a judgment: if F < F0, the sample is uniform; otherwise, the sample is non-uniform. F0 is a constant related to the between-group degrees of freedom m - 1, the within-group degrees of freedom m(n - 1), and the significance level α. The calculation formula is as follows:

[0114] Sum of squares within groups

[0115] Sum of squares between groups

[0116] f e = m(n - 1), within-group degrees of freedom

[0117] f A = m - 1, between-group degrees of freedom

[0118] Within-group variance

[0119] Between-group variance

[0120] Statistic F

[0121] In the formula, x ij is the analysis data of the jth time in the ith group, and x i is the average value of the data in the ith group, is the total average value of the entire data;

[0122] Example 6

[0123] Furthermore, randomly select 30 bottles of gas reference materials Ti-ON-1 to Ti-ON-4, and test each bottle 3 times. Calculate the F value according to the above formula (see Table 3 for details), and compare it with the critical value F0. All are less than the critical value F0, indicating that the gas reference materials prepared in the example have good homogeneity.

[0124] Table 3 Homogeneity of Titanium Alloy Gas Reference Materials in the Example

[0125] Standard sample number parameter O N <![CDATA[F0]]> Ti-ON-1 F 0.47 0.50 1.66 Ti-ON-2 F 0.52 0.48 1.66 Ti-ON-3 F 0.42 0.50 1.66 Ti-ON-4 F 0.65 0.54 1.66

[0126] Fixed value analysis: The original fixed value data were tested using the Grubbs test criterion to eliminate suspicious values, and then the normality of the data distribution was examined. All the test results were in line with the normal or quasi-normal distribution and were selected. The Cochran method was then used to check whether each group of data was of equal precision. After checking, no abnormal data group was found. Then, the standard value and uncertainty were determined according to GB / T15000.3-2008.

Claims

1. Titanium alloy gas analysis standard material, characterized in that: The content range of each element is: A1: 6.0% to 7.0%, V: 4.0% to 4.5%, O: 0.04% to 0.21%, N: 0.004% to 0.012%, the balance is titanium, and the sum of the mass percentages of each component is 100%.

2. The titanium alloy gas analysis standard material according to claim 1, characterized in that: The titanium alloy gas analysis standard substances are composed of the following 4 standard substances composition: (1) Ti-ON-1, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.21±0.02wt%, N: 0.010±0.002wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%; (2) Ti-ON-2, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.15±0.02wt%, N: 0.004±0.001wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%; (3) Ti-ON-3, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.10±0.02wt%, N: 0.008±0.002wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%; (4) Ti-ON-4, the weight percentage of each component is: Al: 6.5±0.2wt%, V: 4.3±0.2wt%, O: 0.04±0.01wt%, N: 0.004±0.001wt%, and the rest is Ti and other impurity elements. The sum of the weight percentages of each component is 100%.

3. The method for preparing a titanium alloy gas analysis standard substance according to claim 1 or 2, characterized in that: Follow the steps below to implement it: Step 1: smelting; V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge are mixed and smelted three times to obtain an ingot; Step 2: Forging; The ingot is subjected to an interactive upsetting and drawing deformation process to obtain a titanium alloy bar of an intermediate billet, and then subjected to a deformation process by a precision forging method to obtain a titanium alloy bar; Step 3: rolling and drawing; The titanium alloy rod is hot rolled and hot drawn three times to obtain titanium alloy wire, and finally the wire is vacuum annealed to relieve stress; Step 4: Shear, mix and package to obtain titanium alloy gas analysis standard material.

4. The method for preparing a titanium alloy gas analysis standard substance according to claim 3, characterized in that: In the step 1, specifically: Step 1.1, ingredients: weigh V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge according to mass percentage, so that the alloy contains 6.0% to 7.0% Al, 4.0% to 4.5% V, 0.04% to 0.21% O, 0.04% to 0.12% N, and the balance is titanium, and the sum of the mass percentages of each component is 100%; V55Al alloy, aluminum beans, titanium dioxide, aluminum nitride and titanium sponge are mixed evenly by an automatic mixer; Step 1.2, according to the number of electrodes to be pressed, the raw materials that have been evenly mixed are evenly divided into the number corresponding to the number of electrodes to be pressed, and pressed into electrodes to obtain an electrode with a specification of Φ100mm×300mm; repeat this step to obtain a plurality of pressed electrode blocks; Step 1.3, placing the obtained several pressed electrodes into a welding box in turn, and when the vacuum degree is drawn to 0.8Pa, filling with argon gas, and when the pressure reaches 6000-8000Pa, using plasma welding to weld the several pressed electrodes into electrode rods; Step 1.4, placing the obtained consumable electrode into a vacuum consumable arc furnace for first smelting; Step 1.5, after surface machining of the obtained primary ingot, a second smelting is performed in a vacuum consumable arc furnace; In step 1.6, the obtained secondary ingot is subjected to surface machining and then smelted for the third time in a vacuum consumable furnace. The obtained finished ingot is subjected to skinning and head cutting and then transferred to the next step for forging.

5. The method for preparing a titanium alloy gas analysis standard substance according to claim 4, characterized in that: During each smelting, the smelting process parameters are: controlling the vacuum degree in the furnace within the range of 0.6-0.8 Pa, controlling the melting rate to 5-30 kg / min, the smelting voltage to 20-40 V, the arc stabilization 2-28 A AC, and the cycle to 12-22 s.

6. The method for preparing a titanium alloy gas analysis standard substance according to claim 3, characterized in that: In the step 2, specifically: The obtained ingot is subjected to an interactive upsetting and drawing deformation process to obtain a titanium alloy bar of an intermediate billet, the forging heating temperature is 1000-1200°C, the initial forging temperature is ≥950°C, the final forging temperature is ≥850°C, the air-cooling forging fire times is 3 times, and the final specification of the bar is Φ130±5mm; Subsequently, the bar is deformed by precision forging, with a forging heating temperature of 900-1100°C, an initial forging temperature ≥850°C, a final forging temperature ≥650°C, air cooling, 1 forging pass, and a final specification of Φ95±3mm. The surface is polished to obtain a titanium alloy bar.

7. The method for preparing a titanium alloy gas analysis standard substance according to claim 3, characterized in that: In the step 3, specifically: Step 3.1, using a reversible rolling mill to complete the rolling of the bar; the rolling heating temperature is 850-1050°C, the initial rolling temperature is ≥800°C, the final rolling temperature is ≥650°C, air cooling, the rolling fire is 2 times, and the final specification of the wire is Φ9.8±0.3mm; Step 3.2, hot drawing the prepared wire, using a tubular furnace for through-heating, the heating temperature is 800-1000°C, after three hot drawing, the final specification of the wire is Φ3.2±0.2mm, the surface is peeled to obtain titanium alloy wire, and finally the wire is vacuum annealed to relieve stress.

8. The method for preparing a titanium alloy gas analysis standard substance according to claim 3, characterized in that: In the step 4, specifically: Step 4.1, shearing the obtained titanium alloy wire to control the particle length to be 3.30-3.55 mm, and the corresponding particle weight to be 0.1000 g-0.1050 g; after shearing, putting the wire into a roller mill for roller milling; Step 4.2, stirring and mixing the tumble-milled particles in an automatic mixer to ensure that the particles are fully mixed; Step 4.3, the mixed particles are cleaned by ultrasonic cleaning in ultrapure water for 5-10 minutes, the number of times is not less than 2 times, then ultrasonic cleaning in anhydrous ethanol for 5-10 minutes, the number of times is not less than 2 times, and finally ultrasonic cleaning in acetone for 5-10 minutes, the number of times is not less than 2 times, to ensure that there is no oil stains and other contaminants on the surface; Step 4.4, packaging the cleaned particles to obtain titanium alloy gas analysis standard substances.